2007
DOI: 10.1007/s10508-007-9213-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Pleasure and Condom Use

Abstract: The purpose of the present study was to determine whether sexually-experienced individuals' pleasure ratings for protected and unprotected vaginal intercourse would be related to actual condom use. College participants (80 women and 35 men, M age = 22.29 years) who reported engaging in vaginal intercourse in the past 3 months completed a questionnaire that assessed their perceptions of the pleasurability of unprotected and condom-protected vaginal intercourse and their own sexual behaviors. Both women and men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
108
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 14 publications
10
108
1
6
Order By: Relevance
“…Sonraki benzer çalışmanın ise 26 yıl sonra literatüre kazandırılmıştır. Kontraseptif yöntemlere ilişkin mitlerin çiftlerin cinsel doyumunu olumsuz etkilediği düşünüldüğünde, 13,[16][17][18][19] bu alandaki çalışma yılları aralığının fazla olması, sayısının sınırlı olması bu sistematik derlemenin dikkat çeken bulgularındandır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Sonraki benzer çalışmanın ise 26 yıl sonra literatüre kazandırılmıştır. Kontraseptif yöntemlere ilişkin mitlerin çiftlerin cinsel doyumunu olumsuz etkilediği düşünüldüğünde, 13,[16][17][18][19] bu alandaki çalışma yılları aralığının fazla olması, sayısının sınırlı olması bu sistematik derlemenin dikkat çeken bulgularındandır.…”
Section: Discussionunclassified
“…8 Literatürde, erkeklerin kullandığı kontraseptif yöntemlere ilişkin mitlerin cinsel sağlık üzerine olumsuz etkiye sahip olduğu ortaya koyulmuştur. 13,[16][17][18] Mitler, özellikle kondom kullanımında sınırlılıklara neden olmaktadır. 18 Yapılan çalışmalarda erkeklerin kondom kullanımına ilişkin en yaygın kaygılarının, cinsel memnuniyetin azalması, 17,19 ereksiyon bozukluğu, enfeksiyon, 13,16,18 bel ağrısı, baş ağrısı, eklem ağrısı 18 ve baş dönmesi 13,16 olduğu saptanmıştır.…”
unclassified
“…However, another study mentioned using condoms is very low in India (10) compared to European countries with a higher level of condom use for protection (26,27). Social workers in India are trying to get condoms more widely used, but sex workers are in a fear of losing their customers if they insist (26) since it is perceived to interfere with the clients´ pleasure of sex (28). So the taboo for such 'condom non-pleasure myth' should be thwarted out.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Randolph, Pinkerton, Bogart, Cecil, and Abramson (2007) found that collegeage men who believed that condoms reduced pleasure were less likely to use condoms. The study authors noted that their study findings supported previous research findings that pleasure is a more important factor for men in the decision to use or not use condoms than it is for women.…”
Section: Discussionmentioning
confidence: 99%